TRENDS IN INCREASING LEGAL LITERACY OF YOUNG PEOPLE IN THE NEW UZBEKISTAN - Barakaev Shokhzod (Bright Mind Publishing, 2025)
In the context of building the New Uzbekistan. It examines the role of legal education in fostering a sense of civic responsibility, rule of law, and awareness of constitutional rights among young people. The study emphasizes the need for comprehensive reforms in the education system, integration of legal knowledge into school curricula, and the use of innovative methods to engage youth in understanding their rights and obligations. Furthermore, the article highlights government initiatives and legislative measures aimed at empowering young citizens to participate actively in the democratic processes and contribute to the development of a law-based state. The findings underscore that enhancing the legal culture of youth is a key factor in ensuring sustainable social progress and the realization of national development goals.
Keywords: Legal literacy, youth, New Uzbekistan, legal education, civic responsibility, constitutional rights, rule of law, legal awareness, democratic participation, legal reforms